Data Dominance as Market Power: Implications within the Framework of Indonesian Competition Law: Dominasi Data Sebagai Market Power: Implikasi dalam Kerangka Hukum Persaingan Usaha di Indonesia - Ari Andy Prastowo; Azzareza Noer Khalifah; Allysa Faras Nabila Rizadian (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The digital economy has transformed traditional sources of market power from capital and market share toward data control as a strategic asset. Specific Background Consumer data has evolved into a central mechanism enabling digital enterprises to build competitive advantages, reinforce dominant positions, and create structural entry barriers through algorithm-driven feedback systems. Knowledge Gap Indonesian competition law, particularly Law No. 5 of 1999, does not explicitly regulate data dominance and remains rooted in a pre-digital paradigm focused on price and market share indicators. Aims This study analyzes how data dominance can be conceptualized as market power within Indonesian competition law and examines its legal implications for enforcement. Results The findings demonstrate that large-scale data control may generate anti-competitive practices, including barriers to entry, ecosystem dependency, and algorithm-based exclusivity, which are not adequately captured by conventional price-based analysis. Novelty This study provides a normative construction that interprets data dominance as a functional form of dominant position within existing legal frameworks without requiring immediate legislative amendment. Implications The study highlights the necessity of interpretative approaches and strengthened institutional capacity to ensure fair competition, while also emphasizing the need for adaptive enforcement mechanisms aligned with digital market structures. Highlights: Large-scale information control creates structural barriers that limit new entrants in digital markets. Algorithm-based feedback mechanisms reinforce ecosystem dependency and concentration of economic control. Existing legal provisions can be reinterpreted to address emerging competition issues without explicit regulatory reform. Keywords: Data Dominance, Market Power, Indonesian Competition Law.